O que se planta se colhe: os entrelaces da Atlas Network com o movimento Escola sem Partido - Lucas Felicetti Rezende (2021)
This work aimed to analyze how the Atlas Network’s pro-market think tanks in Brazil relate to the conservative educational movement Escola sem Partido (ESP). The analyzes start from the premise that the advance of neoliberal rationality on a global scale, since the end of the 20th century, has led to transformations in institutions in line with a free market logic. These transformations prepared the ground for the emergence of a new rationality, neoconservatism, as well as enabling the emergence of new private actors in educational regulation. Neoconservatism is moralizing, a feature that conflicts with neoliberalism's free market amorality, however, both strengthen each other for the diffusion of certain values, such as the prevalence of inequality and State reduction. Some of the new actors in educational regulation are articulated in global networks for the promotion of neoliberal policies and ideals, such as certain think tanks, institutions recognized for influencing the political scene through the mobilization of knowledge. Atlas Network is a think tank that operates within these educational policy networks from its own network of think tanks, which connects more than 460 liberal institutions in about 90 countries. There are 15 think tanks linked to the Atlas network in Brazil, some of which are very intertwined with ESP, such as Instituto Liberal and Instituto Millenium. For ESP, socialist teachers are indoctrinating students for political purposes and, therefore, measures to combat indoctrination should be imposed. Some perceived relationships between Atlas think tanks and ESP took place to strengthen the movement, supporting its growth. This context raises some questions: is the promotion of ESP an Atlas strategy for the dissemination of its ideals? Does ESP relate to all 15 Atlas think tanks in Brazil? How do such relationships occur? In order to answer these questions, the netnography method was used. Through online surveys, various forms of interaction between the Atlas network and ESP were investigated, as well as what those think tanks have mobilized of knowledge about the movement. From the analysis, it was possible to see that the Atlas network nurtured ESP with organizational and ideological support as part of a strategy for the spread of neoliberalism. However, there is no unanimity within the Atlas network on ESP. Among the 15 think tanks, eight have some relation to the movement or have mobilized knowledge about it, some of which distanced themselves from ESP over time and / or criticized it due to its conservative character, distant from the liberal premise. Disagreements over ESP within the Atlas network simultaneously show tensions between neoliberals and neoconservatives, as well as the work of Atlas Network on several fronts to increase its influence and spread ideals of State reduction and more market.